Extraction of microbial chitosan for piezoelectric application - Zamli, Mohamad Izzuddin; Ahmad, Farah; Mohd Hatta, Maziati Akmal (IOP Publishing, 2021)
Chitosan is a natural polysaccharide derived from chitin which is found in the fungus cell walls and crustacean shells. Chitosan has generated a great interest in piezoelectric application because of its interesting properties such as biodegradability, biocompatibility, and low toxicity. The purpose of this study is to focus on the cultivation, fabrication and characterization of chitosan thin film from fungal strain, Aspergillus oryzae cell walls. The fungi was cultivated in bioreactor. Fabrication of chitosan thin film via solvent casting method was optimized via one-factor-at-a-time (OFAT) with 2 parameters (drop-casting volume of solution and drying temperature). Pure chitosan dissolved in formic acid at 0.25 M concentration, dried at 60˚C with 35 mL of solution volume gave the highest mechanical quality factor (3.22) and the lowest dissipation factor (0.327) for thin film fabrication. The optimized fabricate thin film was validated using fungal chitosan and shows the results of mechanical quality factor (3.68) and dissipation factor (0.248) which is comparable to conventional piezopolymer thin film. Therefore, fungal chitosan thin film obtained in this study has the potential to be used in piezoelectric application.